Pengaruh Kompetensi, Independensi Dan Komitmen Organisasi Terhadap Kinerja Auditor Pada Bpkp Perwakilan Diy - Wulandari, Endah; Tjahjono, Heru Kurnianto (208-7721)
Nowadays, a new paradigm emerges which points out the role of an auditor is no longer considered as watch dog to cause fear among auditees. Here, the auditor is taking the role of consultant and catalyst. In term of competence, an auditor can also propose the role of witness or expert witness on a trial. Audit report can be used as a dossiers material in a criminal proceeding by police, district attorney, or court. It proves that audit report is legal evidence that supports a cases completion. At this point, audit report should reflect its auditors competence in which his or her performance will be tested on the court. Auditor, as a profession, is like two sides of a coin. In one sense, auditor is expected to create good public governance. On the other hand, there are risks to deal with, such as, auditeeâs pressure, weaponry threat, and psychological threat. There is also âless harmfulâ threat namely bribery in form of table money or transportation fee. However, these types of threat should not influence the auditors independence in making decision. In addition, there is still so called political influence that may affect the auditors independence. This research aims to analyze the effect of organizational competence, independence, and commitment to auditors performance. Sample of the research was 87 respondents from Finance and Development Supervisory Agency (BPKP) of Yogyakarta Special Province. In answering the researchs hypothesis, the researcher used multiple linear regression analysis, preceded by hypotheses testing. The result shows that competence and independence have significant roles in auditors performance. Additionally, affective and normative commitments give influence to auditors performance. However, continuance commitment does not influence the auditors performance.Â